Risk Factors Related to Operative Duration and Their Relationship With Clinical Outcomes in Pediatric Patients Undergoing Roux-en-Y Hepaticojejunostomy - Yongjun Zhou; Yunfei Zhang; Yunfei Zhang; Yunfei Zhang; Yunfei Zhang; Yunfei Zhang; Yunfei Zhang; Hongjie Guo; Hongjie Guo; Hongjie Guo; Hongjie Guo; Hongjie Guo; et al. (Frontiers Media S.A., 2020)
Background: Operative duration might be important for perioperative morbidity, and its involvement has not been fully characterized in pediatric patients. We identified perioperative variables associated with operative duration and determined their influence on clinical outcomes in pediatric patients.Methods: We retrospectively reviewed 701 patients who underwent elective removal of choledochal cysts followed by Roux-en-Y hepaticojejunostomy. The patients were separated into the long operative time group (>165 min) and short operative time group (<165 min) based on the median operative time (165 min). Propensity score matching was performed to adjust for any potential selection bias. The independent risk factors for operative time were determined using multivariable logistic regression analyses.Results: The operative time was often increased by excision difficulty caused by a larger choledochal cyst size (OR = 1.56; 95% CI, 1.09-2.23; p < 0.001), a greater BMI (OR = 1.02; 95% CI, 1.00-1.15; p = 0.018), and older age (OR = 1.17; 95% CI, 1.02-1.39; p = 0.012) in the multivariate analysis. A long surgical duration was associated with delayed gastrointestinal functional recovery, as measured using the time to first defecation (p = 0.027) and first bowel movement (p = 0.019). Significantly lower levels of serum albumin were found in the long operative time group than in the short operative time group (p = 0.0035). The total length of postoperative hospital stay was longer in patients in the long operative time group (7.51 ± 2.03 days) than in those in the short operative time group (6.72 ± 1.54 days, p = 0.006).Conclusions: Our data demonstrated that a short operative time was associated with favorable postoperative results. The influencing factors of operative time should be ameliorated to achieve better outcomes.